Perspectives on headquarters-subsidiary relationships in the contemporary MNC - Ambos, Tina C.; Ambos, Björn; Birkinshaw, Julian M. (Emerald, 2016)
This volume of Research in Global Strategic Management, the first under the new editorship of William Newburry, provides new perspectives on headquarters-subsidiary relationships in the context of the contemporary multinational corporation. By focusing on the role and the management of subsidiaries, the volume complements recent research on MNC headquarters. Contributions can be grouped into three categories: the management mechanisms of the MNC; tensions and conflicts in HQ-subsidiary relationships; and knowledge transfer in the MNC network.
Keywords: International business enterprises -- Management.; Subsidiary corporations -- Management.; Industrial organization.; elektronické knihy; electronic books